2014
DOI: 10.1097/psy.0000000000000066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Association Between Placental Corticotrophin-Releasing Hormone and Postpartum Depressive Symptoms

Abstract: The current prospective study provides results that reconcile both the positive and negative findings in the existing literature and identifies elevated pCRH as a marker of risk for the development of PPD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 71 publications
6
73
0
1
Order By: Relevance
“…19 In addition, another study found that higher levels of pCRH during mid-pregnancy were associated with depressive symptoms at 3-months postpartum. 20 Together, these studies support the hypothesis that changes in certain HPA markers (sCORT and pCRH) may be associated with increased depressive symptoms in the postpartum period. However, contrary to our hypothesis, we did not find an association between emotional memory during pregnancy and postpartum depressive symptoms.…”
Section: Discussionsupporting
confidence: 65%
“…19 In addition, another study found that higher levels of pCRH during mid-pregnancy were associated with depressive symptoms at 3-months postpartum. 20 Together, these studies support the hypothesis that changes in certain HPA markers (sCORT and pCRH) may be associated with increased depressive symptoms in the postpartum period. However, contrary to our hypothesis, we did not find an association between emotional memory during pregnancy and postpartum depressive symptoms.…”
Section: Discussionsupporting
confidence: 65%
“…Although pregnancy is accompanied by profound changes in the neuroendocrine system, characterized by pituitary gland enlargement, and increases in pituitary peptide output (Glynn et al 2013) and CRH production (Horan et al 2000; Glynn et al 2013), chronic overproduction of glucocorticoid hormones, particularly CRH, before and during pregnancy in women with early life stress, may play a role in higher rates of adverse pregnancy outcomes among these women (Horan et al 2000). This hypothesis is supported by research linking elevated CRH concentrations with increased risk of depression in postpartum (Yim et al 2009; Hahn-Holbrook et al 2013; Glynn and Sandman 2014). …”
Section: Discussionmentioning
confidence: 79%
“…Intra-assay and interassay coefficients ranged from 5% to 15%, respectively. For additional details, see Glynn and Sandman (2014).…”
Section: Methodsmentioning
confidence: 99%